The European and Asian Countries' Philosophy Towards Health Law Reform: A Comparative Review and The Philosophy of Legal Realism - Wulandari, Anggi Yudistia; Gorda , A.A.A Ngurah Sri Rahayu; Kurniawan , I Gede Agus; Gorda , A.A.A Ngurah Tini Rusmini (Universitas Negeri Surabaya, 2024)
Global health issues drive the importance of philosophically based health law reform, with Europe prioritizing social justice and human rights, while Asia combines local traditions and modernization to respond to health challenges adaptively and inclusively. The purpose of this study is to analyze the differences in the principles of health law reform between European and Asian countries and the influence of each region's philosophy on the reform approach based on a review of the philosophy of legal realism. This study uses a normative legal method with a conceptual and legislative approach, analyzing primary, secondary, and tertiary legal materials through document studies and legal interpretation to understand the philosophy, norms, and concepts of health law reform in Europe and Asia based on the philosophy of legal realism. The results of the study show differences in the main principles of health law reform between Europe and Asia, where Europe emphasizes equality, universal access, and social justice, while Asia is more pragmatic by integrating local cultural values and market efficiency; European philosophy focuses on social solidarity and the welfare state, while Asia prioritizes collectivism and adaptation to local contexts, with both reflecting the application of legal realism to meet the needs of society according to their respective social and cultural contexts